2004
DOI: 10.1093/glycob/cwh095
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic binding studies of bivalent oligosaccharides to galectin-1, galectin-3, and the carbohydrate recognition domain of galectin-3

Abstract: Galectins are a growing family of animal lectins with common consensus sequences that bind beta-Gal and LacNAc residues. There are at present 14 members of the galectin family; however, certain galectins possess different structures as well as biological properties. Galectin-1 is a dimer of two homologous carbohydrate recognition domains (CRDs) and possesses apoptotic and proinvasive activities. Galectin-3 consists of a C-terminal CRD and an N-terminal nonlectin domain implicated in the oligomerization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
88
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 47 publications
10
88
0
6
Order By: Relevance
“…1c) and the a3 sialyl-N-Acetyllactosamine (a3 SiaLacNAc) belonging to group (ii) (Fig. 1c), for which a relative decrease and increase in GAL1 binding, respectively, are observed in the presence of the l5-UR domain (binding of these two glycans to GAL1 has been demonstrated previously 31,32 ). In our experimental conditions, the dissociation constant (K D ) of GAL1/LNnT interaction obtained is 51±6 mM, whereas when GAL1 is bound to the l5-UR domain, the K D increases to 130±10 mM, that is, a 2.5-fold decrease in binding affinity of LNnT for GAL1 in the presence of l5-UR (Supplementary Table 1).…”
Section: Gal1 Carbohydrate-binding Specificity When Bound To K5-ursupporting
confidence: 60%
“…1c) and the a3 sialyl-N-Acetyllactosamine (a3 SiaLacNAc) belonging to group (ii) (Fig. 1c), for which a relative decrease and increase in GAL1 binding, respectively, are observed in the presence of the l5-UR domain (binding of these two glycans to GAL1 has been demonstrated previously 31,32 ). In our experimental conditions, the dissociation constant (K D ) of GAL1/LNnT interaction obtained is 51±6 mM, whereas when GAL1 is bound to the l5-UR domain, the K D increases to 130±10 mM, that is, a 2.5-fold decrease in binding affinity of LNnT for GAL1 in the presence of l5-UR (Supplementary Table 1).…”
Section: Gal1 Carbohydrate-binding Specificity When Bound To K5-ursupporting
confidence: 60%
“…that human and bovine dGal-1 bind with relatively poor affinity to extended PLs and that binding affinity is independent of the length of the glycan (44,45). These results were based on isothermal titration microcalorimetry and frontal affinity chromatography, in which glycans are free in solution.…”
Section: Galectin-1 Binding To Terminal N-acetyllactosamine Unitsmentioning
confidence: 99%
“…dGal-1 also binds to glycopeptides containing PL sequences (40,41), glycolipids (42), and neoglycoproteins (43). In contrast to these studies, recent data have suggested that dGal-1 may not recognize PL structures with higher affinity compared with its recognition of short non-extended structures (44,45). Interestingly, dGal-1 has been suggested to bind primarily to nonreducing terminal LN residues rather than to mid-chain LN residues within a PL chain (42,43,46).…”
mentioning
confidence: 99%
See 2 more Smart Citations